Biological Monitoring of Pesticides Exposure in Residents Living Near Agricultural Land. (1st April 2017) - Galea, Karen; MacCalman, Laura; Jones, Kate; Cocker, John; Teedon, Paul; Cherrie, John; van Tongeren, Martie
The authors recently completed a programme of research where they aimed to measure real-life pesticide exposure for adults and children (living within 100m of agricultural land) and to investigate if those exposures increased following the spraying of pesticides. The project also aimed to check whether the methods used in the UK pesticides approval process (at the time of the study) were appropriate for assessing exposure of residents living near fields. In this article a short overview of their research was provided. Recruitment, data and sample collection took place during 2011 and 2012 in three regions judged to be significant arable and orchard growing areas – East Lothian, Kent and Norfolk. Farmers were recruited into the study if they were likely to spray one of the five relevant pesticides (captan, chlormequat, chlorpyrifos, cypermethrin or penconazole) and had residents living within 100m of treated fields. They were asked to provide details of their spray events. Pesticides of relevance to the study were restricted to those likely to be applied during the spray season (taken as being between March and August) for which analytical methods were available for associated urinary biomarkers. Households within 100m of the relevant farmer's field were approached to provide first morning void urine samples (in order to standardise sample collection time and also as this was determined to be the optimal time for urine sample collection) and complete a short accompanying questionnaire during the 48 hours after relevant spray events. Residents also provided additional samples both within and outwith the spraying season (background samples). Twenty-one farms and orchards participated in the study and 156 households including 296 residents were recruited. 3, 275 urine samples and used data from 1, 587 urine samples from 149 residents in the final data analysis were collected. The remaining residents (and their corresponding data and urine samples) were excluded as they did not provide a urine sample which coincided with a spray event involving one of the five relevant pesticides. Pesticide levels in urine samples collected after spray events with the levels in urine provided when no spraying had occurred (background samples) were compared. All results were expressed as creatinine corrected to account for variations in urine sample concentration (creatinine is a natural by-product of metabolism). For captan, cypermethrin and penconazole, over 80% of biomarker concentrations were below the laboratory analysis limit of detection, regardless of whether the urine samples were spray event related, or backgrounds. For chlormequat and chlorpyrifos, the geometric mean urinary biomarker concentrations following spray events were 15.4 μg/g creatinine and 2.1 μg/g creatinine, respectively, compared with 16.6 μg/g creatinine and 2.4 μg/g creatinine for background samples within the spraying season. Outwith the spraying season, concentrations for chlorpyrifos were similar as those within spraying season backgrounds, but for chlormequat, lower concentrations were observed (13.3 μg/g creatinine). There were no statistically significant differences in pesticide biomarker concentrations following spray events between males and females or adults and children. Overall, the results showed that there was no evidence of increased pesticide exposure in residents following a spray event within 100m of their home, when compared to the exposure at times when spraying does not occur. It was considered that the levels of pesticide exposure were low and generally comparable to other population studies, where such data are available. For chlormequat, there is only one other relevant study to compare with these results and this suggests that this population experienced greater exposure than a sub-set of the Swedish population. This is probably due to differences in exposure through the dietary route and it is considered likely that sources such as diet, rather than local spraying events, are responsible for the relatively low urinary pesticide biomarkers detected in this study population. It was concluded that the regulatory exposure assessment methods used at the time of the study and for the spray events assessed were sufficiently conservative.